Physicochemical, morphological, and biological analyses of Ti-15Mo alloy surface modified by laser beam irradiation - Pires, Luana C. [UNESP]; Guastaldi, Fernando P. S. [UNESP]; Nogueira, Andressa V. B. [UNESP]; Oliveira, Nilson T. C.; Guastaldi, Antonio C. [UNESP]; Cirelli, Joni A. [UNESP] (Springer Nature, 2019)
Perform a physicochemical and morphological characterization of a Ti-15Mo alloy surface modified by laser beam irradiation and to evaluate in vitro the morphological response and proliferation of osteoblastic cells seeded onto this alloy. Disks were made of two different metals, Ti-15Mo alloy and cpTi, used as control. A total of four groups were evaluated: polished cpTi (cpTi-pol), laser-irradiated cpTi (cpTi-L), polished Ti-15Mo alloy (Ti-15Mo-pol), and laser-irradiated Ti-15Mo alloy (Ti-15Mo-L). Before and after laser irradiation of the surfaces, physicochemical and morphological analyses were performed: scanning electron microscopy (FEG-SEM), energy-dispersive spectroscopy (EDX), and X-ray diffraction (XRD). The wettability of the samples was evaluated by contact angle measurement. Murine preosteoblastic cells MC3T3-E1 were cultured onto the experimental disks for cell proliferation, morphology, and spreading analyses. Laser groups presented irregular-shaped cavities on its surface and a typical microstructured surface with large depressions (FEG-SEM). The contact angle for both laser groups was 0°, whereas for the polished groups was ≈ 77 and ≈ 78 for cpTi-pol and Ti-15Mo-pol, respectively. Cell proliferation analysis demonstrated a higher metabolic activity in the laser groups (p < 0.05). From the fluorescence microscopy, Ti-15Mo-L surface seems to induce greater cellular differentiation compared to the cpTi-L surface. The preliminary biological in vitro analyses suggested possible advantages of laser surface treatment in the Ti-15Mo alloy regarding cell proliferation and maturation.
Keywords: Cell culture; Dental implants; SEM; Surface modification; Titanium alloys